Ergonomic risk assessment and whole-body vibration measurement in relation with work-related musculoskeletal disorders among food delivery riders in Terengganu, Malaysia - Ahmad, Elyas (2022)
Background: Work-Related Musculoskeletal Disorders (WMSDs) were currently a subject of concern on occupational world where they were the leading cause of major disabilities and absenteeism among the workers. These phenomena affected global economic due to reduce in productivity among the workers. Pandemic Covid-19 had caused major drawback in occupational world where many people lose their job. In Malaysia, food delivery riders became the alternative and popular choice of job especially during pandemic Covid-19 as food delivery services were listed as essential service during Movement Control Orders (MCOs). However, the incidence of Road Traffic Accident (RTA) keeps increasing with high mortality rate among the riders. Many studies had reported the WMSDs were among the factors which contributed to the inappropriate riding behaviour among motorcyclist where WMSDs tend to cause psychological distress among the riders. These eventually lead to inappropriate behaviour such as speeding and violation of traffic light to chase for the trips. Meanwhile, there were many factors was revealed to be significantly associated with development of WMSDs such as working posture and exposure to the chronic vibration. Thus, this study aimed to assess the ergonomic posture using REBA Method and WBV measurement in relation with WMSDs among food delivery riders in Terengganu. Method: A cross-sectional study was conducted among 191 food delivery riders in Terengganu, Malaysia. A snowball sampling method was applied in this study where the “Captain Rider” act as the seed. This study involved answering self-administered questionnaire, REBA assessment and WBV measurement. The self-administered questionnaire contained validated Malay-Translated Standardized Nordic Musculoskeletal Questionnaire (M-SNMQ) which was designed to be completed within 30 minutes. Then, working posture was assessed using REBA method to quantify the risk of WMSDs. Meanwhile, WBV measurement was done using a calibrated Larson Davis HVM 100 Human Vibration Meter with a tri-axial accelerometer seat pad following ISO 2631-1 standards. The data was then analysed using SPSS 20.4 where descriptive analysis, simple and multiple logistic regression were performed. Result: This study revealed high prevalence of WMSDs (74.9%) among the riders which predominant by Low Back Pain (LBP) (73.3%). In addition, the mean (SD) Final REBA Score also was high which was “5”(0.88) indicating of medium risk of developing WMSDs which requires further investigation and the need of change to be done. Furthermore, the mean (SD) of Daily Vibration Exposure, A(8) was also high (0.624 (0.317) m/s2) which exceeded Exposure Action Value (EAV). Three factors were found to be the factors associated with WBV above EAV level which were average working days (aOR=1.56;95% CI=1.11,2.19;p=0.011), presence of WMSDs (aOR=2.93;95% CI=1.37,6.28;p=0.006) and suspension service (aOR=0.39;95%CI=0.19,0.82;p=0.012). This present study also proved that three factor significantly associated with WMSDs development among food delivery riders in Terengganu which were increasing average working days (aOR=2.00; 95% CI=1.34,2.98 ;p=0.001) , WBV above EAV limit (aOR=2.71;95% CI=1.13,6.53;p=0.026), and not doing stretching exercise before work (aOR=21.63; 95% CI=7.45,62.79;p<0.001). Conclusion: The high prevalence of WMSDs among food delivery riders were significantly associated with unergonomic posture which reflected by high REBA score and WBV exceeded EAV level. The result from this study should be used by health sectors as an indicator to implement change and improve the working environment of the riders. Multi-sectoral approach is vital to ensure the prevalence of WMSDs among this neglected group can be reduced which in turn can reduce the incidence of RTA and mortality among the riders.